PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMUNIKASI, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN - Ida Ayu Sri Krisna Dewi; I Gede Riana (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2019)
Employee performance is an important component of the quality of the work of the company that is realized from the work of the employee. A number of things that need to be considered so that employees have optimal performance is the company must pay attention to the factors that affect employee performance. The purpose of this study was to analyze the effect of transformational leadership, communication and compensation on employee performance. This research was conducted at BPR Balaguna Perasta, Klungkung. This study uses a saturated sample method, which uses a total of 36 Balaguna Perasta BPR employees as respondents. Data collection is done through interviews and questionnaire collection. Data analysis using multiple linear regression analysis techniques. The results showed that transformational leadership determines positive and significant impact on employee performance, communication has positive and significant on employee performance, as well as compensation has positive and significant impact on employee performance.